A multi-proxy Holocene palaeoenvironmental record of climate change and prehistoric human activity from Lough Cullin, southeast Ireland. (April 2022) - Kearney, Kevin; Gearey, Benjamin; Hegarty, Susan; Richer, Suzi; Ferreira, Carla; O'Carroll, Ellen; Hamilton, Derek; Eogan, James; McClatchie, Meriel; Armit, Ian; Nagle, Caitlin; Taylor, Kate; et al.
A multiproxy (pollen, microcharcoal, loss-on-ignition, magnetic susceptibility and geochemistry) sequence from Lough Cullin, southeast Ireland, supported by a high-resolution radiocarbon chronology, modelled using Bayesian approaches, provides a record of environmental change for much of the Holocene. Following the establishment of mixed deciduous woodland, climatic deterioration was likely responsible for pronounced vegetation change and erosion, 7615–6500 cal. BC to 6245–5575 cal. BC, evidence for the '8.2 Kyr' BP climate event. The so-called 'elm decline' is dated to 4220–3980 cal. BC and whilst there are possible indications of an anthropogenic cause, clear evidence of woodland clearance with cereal pollen is recorded at 3900–3700 cal. BC, 3790–3580 cal. BC and 3760–3650 cal. BC, during a period of clearance and farming of 320–450 years duration. A reduction in farming/settlement and woodland regeneration during the Middle Neolithic parallels the archaeological record, with low levels of activity during the Late Neolithic/Chalcolithic after 2960–2525 cal. BC, prior to increases during the Bronze Age then woodland clearance and agriculture between 1500–1410 and 1275–1000 cal. BC, corresponding with the archaeological evidence. A subsequent 'step-wise' reduction in human activity follows, from the latter date to 815–685 cal. BC, and a brief but pronounced cessation at 690–535 cal. BC. Renewed woodland clearance and agriculture commenced until 415–250 cal. BC . From the latter date until cal. AD 390–540, the Late Iron Age/Early Medieval period, a phase of woodland recovery is attested, followed by renewed landscape disturbance and arable agriculture in particular, continuing to the close of the record at cal. AD 780–1035 .